Exploring insights in the creative thinking process of prospective mathematics teacher students - Akhsani, Lukmanul; Kartono; Junaedi, Iwan; Asih, Tri Sri Noor (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to examine the effects of differentiated instruction on primary students’ mathematics achievement in the Indonesian context by comparing learning outcomes between classes taught with differentiated instruction and those taught with conventional methods.Method: This quantitative study employed a quasi-experimental, non-equivalent control group design with two intact grade 4 classes from a primary school in Indonesia. The experimental class received differentiated instruction based on students’ readiness, interests, and learning profiles, while the control class received conventional teaching. Data were collected using a validated mathematics achievement test with acceptable reliability. Assumptions were checked, and independent-samples t tests compared posttest achievement between groups.Findings: Students taught with differentiated instruction obtained significantly higher posttest scores than those in the control class, indicating a positive effect on mathematics achievement.Significance: The study provides empirical evidence that differentiated instruction can improve primary mathematics achievement in Indonesian classrooms. The findings offer practical guidance for teachers and inform school leaders and policymakers seeking strategies to enhance learning outcomes